2019
DOI: 10.1002/lt.25377
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Acetaminophen‐Induced Acute Liver Failure Managed Without Intracranial Pressure Monitoring or Transplantation

Abstract: Acetaminophen‐induced acute liver failure (ALF) may require emergency liver transplantation (LT) in the presence of specific criteria, and its management may also include intracranial pressure (ICP) monitoring in selected patients at high risk of cerebral edema. We aimed to test the hypothesis that management of such patients without ICP monitoring or LT would yield outcomes similar to those reported with conventional management. We interrogated a database of all patients treated in an intensive care unit for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Thus, GSH in the liver played an important role in APAP's detoxify. The same conclusion was also made in recent reports where liver GSH was depleted by NAPQI and oxidative stress caused liver injury (Liu et al, 2018;Porteous et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…Thus, GSH in the liver played an important role in APAP's detoxify. The same conclusion was also made in recent reports where liver GSH was depleted by NAPQI and oxidative stress caused liver injury (Liu et al, 2018;Porteous et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…They suggested that LT can be safely performed without fresh frozen plasma with substitution of PCC. � Nonsurgical management of acute liver failure: Porteous et al 55 A single-center retrospective study of 64 adult patients with ALF due to acetaminophen overdose under a conservative medical treatment protocol without use of ICP monitoring or LT showed a survival rate of 79.7%. � Liver Frailty Index score best predicts waitlist mortality: Lai et al 56 Associations were investigated between LFI scores, ascites, and HE and mortality of patients on the LT wait-list at 9 centers in the United States (n ¼ 1044); only frailty was identified as being significantly associated with wait-list mortality.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…54 Porteous and associates provided highly impactful data on the treatment of acute liver failure (ALF) patients. 55 They reviewed their institutional outcomes for 64 adult patients admitted to the ICU with acetaminophen-induced ALF between November 2010 and October 2016 under a conservative medical treatment protocol without use of intracranial pressure (ICP) monitoring or LT. According to their institutional protocol, IV N-acetylcysteine was administered to all patients until discharge from the ICU.…”
Section: Risk Factors and Outcome Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are heterogeneous; they used different strategies to reverse coagulopathy for placement and removal, attempted to correct the coagulopathy for varying periods of time, and did not consistently perform postplacement imaging to diagnose intraparenchymal hemorrhage. While patients with invasive ICP monitors have higher rates of treatment for elevated ICP and may have longer hospital survival, there has been no strong evidence showing improved overall survival to discharge . One center published much better outcomes than generally reported in acetaminophen‐induced ALF managed without invasive ICP monitoring, though their standard treatment of all high‐grade HE included aggressive maneuvers to prevent elevated ICP …”
Section: Invasive Monitoringmentioning
confidence: 99%